2014
DOI: 10.1097/01.prs.0000438460.68098.4b
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Reconstruction Using Tissue-Engineered Alloplastic Implants for Improved Clinical Outcomes

Abstract: These results demonstrate that engineered cartilage tissues can be used as a biological cover for an alloplastic implant. This system may improve the structural and functional interactions between the implant and the recipient's tissues and thus enhance the outcome of total auricular reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In the years since many research groups have published on the manufacture of structures from soft solids some of which allow for the incorporation of cells . Most recently, Hwang et al reported the production of a cartilage‐like structure for auricular reconstruction . Notably, the majority of additively manufactured soft‐solid structures exhibit relatively low complexity and are typically broader at their base than at their peak to reduce the risk of the structure collapsing.…”
mentioning
confidence: 99%
“…In the years since many research groups have published on the manufacture of structures from soft solids some of which allow for the incorporation of cells . Most recently, Hwang et al reported the production of a cartilage‐like structure for auricular reconstruction . Notably, the majority of additively manufactured soft‐solid structures exhibit relatively low complexity and are typically broader at their base than at their peak to reduce the risk of the structure collapsing.…”
mentioning
confidence: 99%
“…There is a narrow gap between the scalp and ear cartilage. Therefore, it is necessary to widen the gap by augmentation of the mastoid where the ear diverges from scalp [ 4 ]. Currently, use of autologous costal cartilage is the standard treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…These implants showed no evidence of skin necrosis, implant exposure, or extrusion compared with nonseeded controls after implantation into the dorsum of athymic mice. 68 One human study used injection implantation of cultured chondrocytes into the subcutaneous pocket on the fascia of the lower abdomen. Six months later, the neocartilage block was surgically harvested and carved into an auricle for implantation.…”
Section: Applications In Craniofacial Reconstruction and Plastic Surgerymentioning
confidence: 99%